PRR5L degradation promotes mTORC2-mediated PKC-δ phosphorylation and cell migration downstream of Gα12 - Gan, Xiaoqing; Offermanns, Stefan (Nature cell biology, 2012)
Mammalian target of rapamycin complex 2 (mTORC2) phosphorylates AGC protein kinases including protein kinase C (PKC) and regulates cellular functions such as cell migration. However, its regulation remains poorly understood. Here we show that lysophosphatidic acid (LPA) induces two phases of PKC-δ hydrophobic motif phosphorylation. The late phase is mediated by Gα12, which specifically activates ARAF, leading to upregulation of the RFFL E3 ubiquitin ligase and subsequent ubiquitylation and degradation of the PRR5L subunit of mTORC2. Destabilization of PRR5L, a suppressor of mTORC2-mediated hydrophobic motif phosphorylation of PKC-δ, but not AKT, results in PKC-δ hydrophobic motif phosphorylation and activation. This Gα12-mediated signalling pathway for mTORC2 regulation is critically important for fibroblast migration and pulmonary fibrosis development.
Im Titel ist "12" in Gα12 tiefgestellt
Gesehen am 07.11.2018